2020
DOI: 10.1038/s41598-020-71918-7
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic analysis in old Montenegrin vineyards reveals ancient ways currently active to generate diversity in Vitis vinifera

Abstract: Global viticulture has evolved following market trends, causing loss of cultivar diversity and traditional practices. In Montenegro, modern viticulture co-exists with a traditional viticulture that still maintains ancient practices and exploits local cultivars. As a result, this region provides a unique opportunity to explore processes increasing genetic diversity. To evaluate the diversity of Montenegrin grapevines and the processes involved in their diversification, we collected and analyzed 419 samples in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 59 publications
1
18
3
1
Order By: Relevance
“…However, our results provide genome-level evidence that Western European wine varieties did not originate from independent domestication, but rather from a post-domestication hybridization event. Compared to insights generated from markers with ascertainment bias, our data contradicts previous claims for an independent domestication (4, 13, 3134), and helps clarify ambivalent hypothesis (6, 35-38), in favor of a post-domestication hybridization model (14, 39). Furthermore, our results suggest a common domestication framework that contemplates both wine and table grapes deriving from the historically and genetically accepted domestication center in the Transcaucasus, followed by expansion of grapevine across the Mediterranean basin, where it hybridized at least once with local sylvestris populations (Fig.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…However, our results provide genome-level evidence that Western European wine varieties did not originate from independent domestication, but rather from a post-domestication hybridization event. Compared to insights generated from markers with ascertainment bias, our data contradicts previous claims for an independent domestication (4, 13, 3134), and helps clarify ambivalent hypothesis (6, 35-38), in favor of a post-domestication hybridization model (14, 39). Furthermore, our results suggest a common domestication framework that contemplates both wine and table grapes deriving from the historically and genetically accepted domestication center in the Transcaucasus, followed by expansion of grapevine across the Mediterranean basin, where it hybridized at least once with local sylvestris populations (Fig.…”
Section: Discussioncontrasting
confidence: 95%
“…3E). Non-genome-level studies have suggested a genetic relatedness with local wild genotypes in cultivated varieties from Italy, France and the Balkans (6, 13, 36, 38, 43, 44), but whether these signatures reflect a single or multiple hybridization events remains to be established. Future whole genome resequencing efforts across the Mediterranean distribution range will be vital to expand our knowledge on post-domestication hybridization, particularly in the wine-producing varieties of Western Europe.…”
Section: Discussionmentioning
confidence: 99%
“…of putative secondary domestication centers along the main migration routes due to genetic relationships between wild and cultivated accessions, especially in the Mediterranean Basin and Central Asia (Grassi et al, 2003;Arroyo-García et al, 2006;Myles et al, 2011;Zhou et al, 2017;Riaz et al, 2018). The coexistence of wild populations together with domesticated ones is often and the bidirectional gene flow (wild-to-cultivated and cultivated-towild) has been well documented (De Andrés et al, 2012;Ekhvaia et al, 2014;Riaz et al, 2018;D'Onofrio, 2020;Maraš et al, 2020), supporting the occurrence of secondary domestication events from local wild populations or introgression events. These events, the geographical origin and human usage were found to strongly shape the genetic structure of grapevine germplasm (Bacilieri et al, 2013).…”
Section: South Caucasus the First Grapevine Domestication Centermentioning
confidence: 96%
“…In the grapevine, the coexistence of wild populations and domesticated varieties is well-documented with a bidirectional gene flow (De Andrés et al, 2012;Riaz et al, 2018;D'Onofrio, 2020;Maraš et al, 2020). The consequent generations overlapping due to hybridization events between wild and modern varieties implied stratification that cannot be resolved on a time scale, as revealed by pedigree analysis (Lacombe et al, 2012;D'Onofrio, 2020).…”
Section: Discussionmentioning
confidence: 99%